Systemic and mucosal antibodies to Klebsiella in patients with ankylosing spondylitis and Crohn's disease. Issue 12 (December 1992) - O'Mahony, S; Anderson, N; Nuki, G; Ferguson, A
Abstract : Whole gut lavage fluid is a useful source of material for the study of intestinal immunity and inflammation in humans. Systemic and mucosal antibodies to Klebsiella pneumoniae were measured by enzyme linked immunosorbent assay (ELISA) in serum samples and whole gut lavage fluid from 14 patients with ankylosing spondylitis, 14 with Crohn's disease, and 16 immunologically normal controls. As the concentration of IgG in whole gut lavage fluid reflects disease activity in Crohn's disease, this approach was used to detect intestinal inflammation in patients with ankylosing spondylitis who also had disease activity and use of non-steroidal anti-inflammatory drugs (NSAIDs) recorded. Small intestinal permeability to cellobiose and mannitol was also studied. In serum samples, levels of IgA antibody to klebsiella were high in patients with Crohn's disease and in patients with active ankylosing spondylitis, and were significantly correlated with the erythrocyte sedimentation rate in patients with ankylosing spondylitis. Levels of IgG antibody to klebsiella were also high in patients with Crohn's disease. Studies of whole gut lavage fluid showed similar levels of IgA antibody to klebsiella in the three study groups, but levels of whole gut lavage fluid IgM and IgG antibodies to klebsiella were high in patients with Crohn's disease. Levels of IgG in whole gut lavage fluid were high in patients with Crohn's disease but in only one patient with ankylosing spondylitis, though the cellobiose/mannitol permeability ratio was abnormal in eight of 13 patients with ankylosing spondylitis. It is concluded that high levels of serum IgA antibody to klebsiella are not specific to ankylosing spondylitis, and that there is no evidence of an abnormal intestinal IgA antibody response to klebsiella in patients with ankylosing spondylitis.